730 Prediction of type 4a myocardial infarction with the angiography-derived haemodynamic (added) index. (8th December 2021) - Viscusi, Michele Mattia; Mangiacapra, Fabio; Rinaldi, Raffaele; Colaiori, Iginio; Sticchi, Alessandro; Paolucci, Luca; Russo, Massimo; Nusca, Annunziata; Melfi, Rosetta; Ricottini, Elisabetta; Gallo, Paolo; Ussia, Gian Paolo; et al.
Abstract: Aims: Percutaneous coronary intervention (PCI) is frequently complicated by type 4a myocardial infarction (MI). We assessed the usefulness of the angiography-derived haemodynamic index (ADDED) index in predicting type 4a MI in patients with chronic coronary syndrome (CCS) undergoing PCI. Methods and results: We enrolled 442 patients treated with single-vessel PCI. The ADDED index was calculated as the ratio of the Duke Jeopardy Score (DJS) to the minimum lumen diameter (MLD) assessed with quantitative angiography analysis (QCA). Patients in the higher ADDED tertile presented higher occurrence of type 4a MI (17.7%, P  < 0.0001). At ROC curve analysis, the ADDED index could significantly discriminate between patients with and without type 4a MI (area under the curve 0.745). At multivariate analysis, an ADDED index value >5.25 was the strongest independent predictor type 4a MI. Conclusions: Our results support the role of the ADDED index as a predictor of type 4a MI in patients with CCS treated with elective PCI.